A Follow-Up Community Survey of Knowledge and Beliefs About Cancer and Genetics - Sweeney, Shannon M. (J Cancer Educ, 2016)
The purpose of this study is to assess changes since the launch of the US Surgeon General’s campaign in the public’s beliefs about the role of genetics in the etiology of cancer, as well as changes in recording family health history. We conducted a survey of 480 Western New York adults, assessing: (1) experiences with cancer, (2) beliefs about cancer and genetics, and (3) practices of recording family health history. Most respondents were aware of the importance of family history. The sample also showed increased knowledge about cancer and genetics compared with a previous survey. However, only 7 % kept written records that included medical conditions, which was not different from a previous survey. Time constraints, apathy, and reluctance to find out negative health information were the most reported barriers. Results suggest a need for continued education of the public, with increased emphasis on written family health records.